2023
DOI: 10.1093/alcalc/agad028
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mental health and alcohol use across profiles of COVID-19 disruptions

Abstract: This study aimed to examine differences in mental health and alcohol use outcomes across distinct patterns of work, home, and social life disruptions associated with the COVID-19 pandemic. Data from 2093 adult participants were collected from September 2020 to April 2021 as a part of a larger study examining the impacts of the COVID-19 pandemic on substance use. Participants provided data on COVID-19 pandemic experiences, mental health outcomes, media consumption, and alcohol use at baseline. Alcohol use diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…To that end, several psychosocial models of COVID-19-related stress have been proposed, with extant conceptualizations often focusing on the impact of the pandemic on occupational, domestic, and social domains. Research examining these general psychosocial models has found unique profiles of responding across domains and associations between particular profiles and alcohol use problems (Gray et al, 2023;Luk et al, 2023), suggesting nuanced and important relations between COVID-19-related stress and substance misuse. In an attempt to better understand cognitive and behavioral factors underlying COVID-19-related stress, several interrelated psychological processes-collectively referred to as the COVID stress syndrome-have been proposed as significant risk factors for pandemic-related substance misuse (McKay & Asmundson, 2020;Taylor et al, 2020a).…”
Section: Profile Analysis Of Covid Stress Scalesmentioning
confidence: 99%
“…To that end, several psychosocial models of COVID-19-related stress have been proposed, with extant conceptualizations often focusing on the impact of the pandemic on occupational, domestic, and social domains. Research examining these general psychosocial models has found unique profiles of responding across domains and associations between particular profiles and alcohol use problems (Gray et al, 2023;Luk et al, 2023), suggesting nuanced and important relations between COVID-19-related stress and substance misuse. In an attempt to better understand cognitive and behavioral factors underlying COVID-19-related stress, several interrelated psychological processes-collectively referred to as the COVID stress syndrome-have been proposed as significant risk factors for pandemic-related substance misuse (McKay & Asmundson, 2020;Taylor et al, 2020a).…”
Section: Profile Analysis Of Covid Stress Scalesmentioning
confidence: 99%